Effect of Natural Lipid on Flowering, Pollination Traits and Fruit Set on Loquat (Eriobotrya japonica Lindl.) - Demirkeser, T.H.; Polat, A.A.; Caliskan, O. (Asian Journal of Chemistry, 2010)
In this study, the possible effects of lysophosphatidylethanolamine when applied onto eight-year-old Eriobotrya japonica Lindl. loquat cultivar is investigated. Treatments included both single and double applications of lysophosphatidylethanolamine sprayed before bloom and an untreated control. The treated buds were sampled from trees for laboratory pollen experiment and the trees were observed for several flowering, fruit set and harvest traits. In laboratory experiment, the pollen grains were sowed on media having various sucrose concentrations (5, 10, 15 and 20 %) and incubated on 10, 15 and 20 °C. It was observed that pollen germination and tube growth increased on 15 and 20 °C incubation temperatures and 10 and 20 % concentrations. The experiment also indicated that single lysophosphatidylethanolamine application increased the pollen viability rate (%). Pollen germination rate (%) and pollen tube growth were negatively affected by lysophosphatidylethanolamine treatments when evaluated after 3, 6 and 9 h incubation. The field observations indicated that lysophosphatidylethanolamine conditioned earliness for flowering and harvest date. The double application also had significantly higher fruit set comparing the control. Taken together, the results indicate that lysophosphatidylethanolamine applications may be beneficial for fruit set and earliness in loquat production.